2008
DOI: 10.1515/epoly.2008.8.1.1569
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of a spinnable phase change material CDA-IPDI-MPEG

Abstract: A comb like phase change material (PCM) CDA-IPDI-MPEG, based on cellulose diacetate (CDA) as a backbone, with methoxy polyethylene glycol (MPEG) grafted onto it, was synthesized by a two-step reaction in the presence of dibutyltin dilaurate (DBTDL) catalyst system, using acetone as solvent and isophorone diisocyanate (IPDI) as crosslinking reagent. Size exclusion chromatography (SEC) was used to characterize the molecular weight distribution of each step reaction products. Back titration was utilized for deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Thus, synthesis of novel SSPCMs with high phase change enthalpy and low phase change temperature is a significant and pressing work. Recently, the preparation and application of polymeric SSPCMs has arose growing interests of considerable scientists [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], and many novel polymeric SSPCMs were obtained by chemical grafting, blocking and crosslinking copolymerization using the solid frameworks as a hard segment and SLPCMs as a soft segment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, synthesis of novel SSPCMs with high phase change enthalpy and low phase change temperature is a significant and pressing work. Recently, the preparation and application of polymeric SSPCMs has arose growing interests of considerable scientists [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], and many novel polymeric SSPCMs were obtained by chemical grafting, blocking and crosslinking copolymerization using the solid frameworks as a hard segment and SLPCMs as a soft segment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they are usually used as the phase change functional chains (soft segment) in the molecule of polymeric SSPCMs [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Jiang et al [17] reported a series of SSPCMs by grafting polymerization in which CDA acted as the main chain and PEG with different molecular weights acted as the grafting side chain.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the melting peak temperature of the products of Cheng et al (2008) and Li et al (2009) are 52.9°C and 40.7-60.1°C respectively, while the results of this work are in the range of 28.2-28.6°C. According to the literature, the difference between the melting and crystallization temperatures of CDA-IPDI-MPEG SSPCMs (Cheng et al 2008) is 24.3°C, and that of cellulose-g-MPEG SSPCMs (Li et al 2009) is in the range of 14.7-4.1°C. As can be seen in Table 6, the difference between T mp and T cp of Cellulose-g-E 2 C 16 copolymers is in the range of 13.7-15.3°C.…”
Section: Optimization Of Reaction Conditionsmentioning
confidence: 50%
“…The transition temperature and enthalpy of cellulose-g-mPEG could be adjusted by changing the molecular weight and the content of mPEG side chains. Cheng et al (2008) prepared cellulose diacetate-isophorone diisocyanate-poly(-ethylene glycol) monomethyl ether (CDA-IPDI-MPEG) SSPCMs through a two-step reaction and determined its melting enthalpy (DH m ) and crystallization enthalpy (DH c ) to be 25.45 and 24.86 J/g and its melting temperature (T m ) and crystallization temperature (T c ) to be 52.9 and 28.6°C, respectively. Chen et al (2014) systematically investigated the effect of different synthetic pathways on the phase transition behavior of cellulose ethers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation